2013
DOI: 10.1177/2165143413486693
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Transition to Adult Life for Youth With Intellectual Disabilities

Abstract: A number of best practices are recommended by researchers and professionals in the field of transition to improve postschool outcomes for youth with intellectual disabilities. This study analyzed data from the National Longitudinal Transition Study-2 to examine whether best practices are predictive of postschool outcomes. The combination of five best practices was found to significantly predict employment, postsecondary education, and enjoyment of life outcomes after controlling for characteristics. In these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 27 publications
4
63
1
5
Order By: Relevance
“…The path from parent expectations to outcomes was not only statistically nonsignificant, but the magnitude of the standardized parameter estimate was very close to zero. This is a surprising finding that is inconsistent with previously published literature that has suggested that parent expectations predict outcomes for individuals with ID (Carter et al, 2012;Doren et al, 2012;Papay & Bambara, 2014). Because of this, we attempted to explore alternative explanations for why this may have occurred.…”
Section: Department Ofcontrasting
confidence: 56%
See 2 more Smart Citations
“…The path from parent expectations to outcomes was not only statistically nonsignificant, but the magnitude of the standardized parameter estimate was very close to zero. This is a surprising finding that is inconsistent with previously published literature that has suggested that parent expectations predict outcomes for individuals with ID (Carter et al, 2012;Doren et al, 2012;Papay & Bambara, 2014). Because of this, we attempted to explore alternative explanations for why this may have occurred.…”
Section: Department Ofcontrasting
confidence: 56%
“…In students with severe disabilities, parent expectations about employment predicted the likelihood that an individual would gain employment following graduation (Carter et al, 2012). In students with intellectual disability, Papay and Bambara (2014) found that parent expectations for employment and postsecondary education were among the strongest predictors of those outcomes. Parent expectations have also been shown to be significant predictors of high school graduation rates and employment after high school across students from all disability categories (Doren, Gau, & Lindstrom, 2012).…”
Section: Factors Associated With Positive Adult Life Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…Deaf adolescents whose parents held higher expectations about their future did not only demonstrate stronger autonomous orientations, but also had higher numbers of early employment experiences and found jobs independently. The finding that parental expectations did not have a direct effect on occupational outcomes for deaf individuals appears to counter research that suggests otherwise (e.g., Doren et al 2012;Papay and Bambara 2013;Wehman et al 2014), but supports the proposal that adolescents' self-determination mediates the relationship between parent expectations and child outcomes (Soenens and Vansteenkiste 2005). Parental expectations had a significant indirect effect on only one employment outcome, that of wages earned, which was mediated through their child's autonomous orientations.…”
Section: Parent Expectations: Antecedents Of Autonomous Orientations mentioning
confidence: 40%
“…Immediately after high school completion, parental expectations also increase the likelihood of collegiate enrollment (Chiang et al 2012;Doren et al 2012;Papay and Bambara 2013). Parental expectations are also linked to occupational attainment (Blustein et al 2002;DiRago and Vaillant 2007;Doren et al 2012;Papay and Bambara 2013;Wehman et al 2014), which suggests that parental beliefs and attitudes have long-ranging implications over longer periods of time. Yet, the exact mechanisms behind the relationship of parental expectations with outcomes are still being investigated.…”
Section: Autonomy Developmentmentioning
confidence: 94%